Complete Genome Sequence of a Pseudomonas simiae Strain with Biocontrol Potential against Aphanomyces Root Rot - Godebo, Ashebir T. (Microbiol Resour Announc, 2021)
Aphanomyces euteiches is a soilborne plant pathogen. It causes severe root rot in leguminous crop species. We report the complete genome sequence of a biocontrol strain, Pseudomonas simiae K-Hf-L9. The strain inhibited Aphanomyces euteiches mycelia and zoospores and suppressed root rot in field peas grown under controlled growth chamber conditions.